Level of Agreement, Reliability, and Minimal Detectable Change of the MusclelabTM Laser Speed Device on Force-Velocity-Power Sprint Profiles in Division II Collegiate Athletes - Jamie J. Ghigiarelli; Keith J. Ferrara; Kevin M. Poblete; Carl F. Valle; Adam M. Gonzalez; Katie M. Sell (MDPI AG, 2022)
This study examined the level of agreement (Pearson product-moment correlation [rP]), within- and between-day reliability (intraclass correlation coefficient [ICC]), and minimal detectable change of the MusclelabTM Laser Speed (MLS) device on sprint time and force-velocity-power profiles in Division II Collegiate athletes. Twenty-two athletes (soccer = 17, basketball = 2, volleyball = 3; 20.1 ± 1.5 y; 1.71 ± 0.11 m; 70.7 ± 12.5 kg) performed three 30-m (m) sprints on two separate occasions (seven days apart). Six time splits (5, 10, 15, 20, 25, and 30 m), horizontal force (HZT F0; N∙kg−1), peak velocity (VMAX; m∙s−1), horizontal power (HZT P0; W∙kg−1), and force-velocity slope (SFV; N·s·m−1·kg−1) were measured. Sprint data for the MLS were compared to the previously validated MySprint (MySp) app to assess for level of agreement. The MLS reported good to excellent reliability for within- and between-day trials (ICC = 0.69-0.98, ICC = 0.77-0.98, respectively). Despite a low level of agreement with HZT F0 (rP = 0.44), the MLS had moderate to excellent agreement across nine variables (rp = 0.68-0.98). Bland-Altman plots displayed significant proportional bias for VMAX (mean difference = 0.31 m∙s−1, MLS < MySp). Overall, the MLS is in agreement with the MySp app and is a reliable device for assessing sprint times, VMAX, HZT P0, and SFV. Proportional bias should be considered for VMAX when comparing the MLS to the MySp app.